Major Pulmonary Disorders Leading Intensive Care Unit Admission in Pregnancy - Ezgi Özyılmaz; Tuncay Nas (Medical Network, 2008)
Respiratory insufficiency is one of the most frequent causes of intensive care unit (ICU) admissions among obstetric patients. The challenges faced in the treatment of this patient population are even greater due to the fact that there are two young lives to be saved simultaneously: mother and fetus. Any treatment which may be the best choice for the mother may adversely affect the fetus. The aim of this review is to summarize the reasons and the management of the most common pulmonary disorders requiring ICU admissions in pregnancy for the obstetrician. In the spectrum of this review the most common reasons of respiratory failure such as bronchial asthma, pulmonary embolism, amnion fluid embolism and pneumonia will be discussed. Optimal management for all of the disorders requires early identification and treatment of the respiratory failure, stabilizing the hemodynamics, improve oxygenation and close fetal and maternal monitoring.